Ultrastructural characteristics of primary renal epithelial tumours with granular oncocytic cytoplasm - Trivunić Dajko, Sandra; Bogdanović, Jovo; Andrejić Višnjić, Bojana; Popović, Milan; Hes, Ondrej (Vojnosanitetski pregled, 2021)
Abstract Background/Aim. Ultrastructural analysis of tumours has shown many common characteristics of certain neoplasms, as well as their specificities. Primary renal epithelial tumours with granular oncocytic cytoplasm is a very heterogeneous group in their histological origin and biological behaviour, which results in a difference in treatment and prognosis of the disease, making accurate morphological diagnosis necessary. The aim of this study was to determine ultrastructural similarities and differences among primary renal epithelial tumours with granular oncocytic cytoplasm. Methods. The analysis of archival and routine material in the archives of the Department of Pathology, University Hospital in Plzen, Czech Republic, as well as archival and routine material in the Centre for Pathology and Histology, Clinical Centre of Vojvodina in Novi Sad, discovered 346 primary renal epithelial tumours with granular oncocytic cytoplasm and divided them into 5 groups: 1) renal oncocytoma (RO) (234 tumours), 2) oncocytic papillary renal cell carcinoma (O-PRCC) (12 tumours), 3. sporadic renal hybrid oncocytic/chromophobe tumour (HOCT) without evidence of Birt Hogg Dubé syndrome (BHD) (14 tumours), 4) chromophobe renal cell carcinoma (ChRCC) (21 tumours) and 5) granular renal cell carcinoma (RCC) [64 tumours + 1 clear cell RCC (CRCC) with hyaline globules]. Ultrastructural analysis of tumour cells at the subcellular level was done using electron microscope (Philips electron microscope TEM 208) at the Department of Pathology, University Hospital in Plzen, Czech Republic. Cellular organelles and pigments were evaluated in 5 tumours from each group according to the simple random sample principle with a total of 30 analysed tumours. Results. In all analysed primary renal epithelial tumours with granular oncocytic, cytoplasm dominant organelles were mitochondria. Specific ultrastructural characteristics of RO were round mitochondria with lamellar cristae, whereas ChRCC had numerous typical cytoplasmic microvesicles 100–700 nm large and mitochondria with tubulovesicular, lamellar and circular cristae. Ultrastructural specificity of hybrid tumours were rare microvesicles and numerous mitochondria of O-PRCC mitochondria with lamellar cristae and small intracytoplasmic vesicles, 100–200 nm large, and of granular RCC, in addition to mitochondria, also glassy hyaline globules (GHG). Conclusion. Ultrastructural analysis indicates mitochondria as the dominant organelle in the analysed tumours. Electron microscopy showed specificities, i.e., differences in appearance of cristae, presence and size of vesicles as well as deposition of pigment in and out of cytoplasm and glassy hyaline globules.
Keywords: kidney neoplasms; microscopy, electron; diagnosis, differential; mitochondria; cytoplasmic granules